The KEAP1–NRF2 System in Cancer - Taguchi, Keiko; Yamamoto, Masayuki (Frontiers in Oncology, 2017)
Cancer cells first adapt to the microenvironment and then propagate. Mutations in tumor suppressor genes or oncogenes are frequently found in cancer cells. Comprehensive genomic analyses have identified somatic mutations and other alterations in the KEAP1 or NRF2 genes and in well-known tumor suppressor genes or oncogenes, such as TP53, CDKN2A, PTEN, and PIK3CA, in various types of cancer. Aberrant NRF2 activation in cancer cells occurs through somatic mutations in the KEAP1 or NRF2 gene as well as through other mechanisms that disrupt the binding of KEAP1 to NRF2. Unregulated NRF2 confers on cancer cells high-level resistance to anti-cancer drugs and reactive oxygen species (ROS) and directs cancer cells toward metabolic reprogramming. Therefore, NRF2 has been studied as a therapeutic target molecule in cancer. Two strategies have been used to target NRF2 via therapeutic drugs: inhibition of NRF2 and induction of NRF2. NRF2 inhibitors may be effective against NRF2-addicted cancer cells in which NRF2 is aberrantly activated. These inhibitors have not yet been established as NRF2-targeted anti-cancer drugs for the treatment of human cancers. Diagnosis of NRF2 activation could facilitate the use of NRF2 inhibitors for the treatment of patients with NRF2-addicted cancers. Conversely, NRF2 inducers have been used or are being developed for non-cancer diseases. In addition, NRF2 inducers may be useful for cancer chemotherapy in combination with conventional anti-cancer agents or even NRF2 inhibitors.